The Effect of Ramadan Fasting on Vo₂Max of Futsal Club Kawat Duri Athletes in Malang City Through the Bleep Test - Dhimas Zainurrosyid; Olivia Andiana (Indonesian Conditioning Coaches, 2026)
This study aims to determine the effect of Ramadan fasting on the VO₂Max capacity of futsal athletes from Kawat Duri Club in Malang City. Using a quantitative approach and a quasi-experimental pre-test post-test design, this study involved 10 athletes aged 16–18 years selected through purposive sampling. Data were collected using the bleep test conducted before and after the month of Ramadan. Data analysis was carried out using normality tests, homogeneity tests, and paired t-tests with SPSS software. The results showed that 7 out of 10 athletes experienced an increase in VO₂Max values after fasting, while 3 athletes showed unchanged results. The t-test results produced a significance value of < 0.001, indicating that there is a significant difference between VO₂Max values before and after fasting. These findings indicate that Ramadan fasting can have a positive impact on improving athletes' aerobic capacity, as long as it is balanced with consistent physical training and proper nutrition management. Therefore, fasting does not become an obstacle in maintaining or even enhancing the physical fitness performance of futsal athletes, particularly in terms of VO₂Max, but rather can serve as a stimulus for beneficial physiological adaptations.